تداعيات الأزمة المالية العالمية وانعكاساتها على الفكر المحاسبي (المجلة العراقية للعلوم الاقتصادية, 2018)
The world passed with international financial crisis led to the collapse of most financial institution . Also this collapse affected most countries in the world . This crisis started in USA and moved its impact to Europe and east Asia countries and it reached even to Arabic states .This crisis impacted on different industrial sectors and even it camiecl damage to commercial and services as well as humatairain institutions .There were many reasons or factors behind the happening of this crisis, and one of them was the accounting , administrative and financial corruption which were spread in these institutions .From this view the idea of the research is coming out to show the role of this crisis on accounting thinking especially one of the reasons of this crisis is accountive one and the claim that the accounting standards one behind this crisis ( or the main cause for this crisis).Thus the research shows the reasons of this crisis and how does it reflect on the accounting thinking.